Differences in the levels of repetitive strength of young footballers - Smajic, M.; Madic, D.; Molnar, S.; Dimitric, G.; Tomic, B.; Radosav, S. (3rd International Scientific Conference: Exercise and quality of life. April 12/13th 2013, 2013)
Training viewed as a transformation process requires a player`s great effort under difficult conditions, as well as extremely developed abilities and characteristics necessary for achieving success in football. In order to preserve a good quality of football, which has evidently fallen due to disorganized or failed systematic selection, special attention should be given to work with younger age categories of footballers. The mission of science in this matter is to determine particular principles and rules of transformation processes of anthropological characteristics important for football, while the training technology should find the most optimal training contents (aids, methods, and loads) for transformation of the above characteristics. The purpose of this research is to determine differences in the levels of repetitive strength of young footballers. The research sample included 120 footballers of different age categories from the football club "Vojvodina" (30 under 12s (11.5±0.5), 30 under 14s (13.5±0.5), 30 under 16s (15.5±0.5), and 30 under 18s (17.5±0.5). For the evaluation of the level of repetitive strength of young footballers tests push-ups and sit-ups were applied. Testing the significance of differences between young footballers at different age categories, as well as deviation from expected values, was calculated by the t-test and univariate analysis of variance (ANOVA). According to the obtained results we can conclude that average results show general tendency of improving the results of younger towards older age categories (with the exception of in the push-up test where U12s have better average results than the U14s). The measuring of variability indicates that in the push-up test U18s are most homogeneous and most heterogeneous are U14s, while in the sit-up test most homogeneous are U18s and U12s are most heterogeneous. In the push-up test, there are statistically significant differences between U14s and U18s (level of significance p=0.05), while in other age categories differences of arithmetic means are not statistically significant and in the sit-up test there are no statistically significant differences between the different age categories.